The Impact of Managerial Overconfidence on Capital Structure: Empirical Evidences in Vietnam - Pham, Viet Quoc; Nguyen, Dinh Trung (International Journal of Economics and Financial Issues, 2019)
This paper studies the effects of the managerial overconfidence on the corporate capital structure in the Vietnamese stock market for the period 2010 - 2016 by estimating generalized least squares (GLS) on a sample of 329 non-financial firms listed on the Ho Chi Minh city Securities Exchange (HOSE). Research results show that managerial overconfidence has an impact on corporate capital structure, in particular firms with overconfident managers have higher overall leverage and short-term liabilities, but tend to reduce long-term debt ratio. In addition, state-owned enterprises having overconfident managers experience higher long-term debt ratios than other enterprises. Keywords: Capital Structure, Managerial Overconfidence, Non-financial listed firms, Vietnam. JEL Classifications: G41, G32 DOI: https://doi.org/10.32479/ijefi.8862